2020
DOI: 10.3390/jcm9103377
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Infarction in Centenarians. Data from The Polish Registry of Acute Coronary Syndromes

Abstract: Background: There are no data regarding the mortality rate, risks and benefits of particular reperfusion methods and pharmacological treatment complications in patients aged over 100 years with acute coronary syndromes. We sought to assess the treatment of myocardial infarction (MI) in patients older than 100 years and to determine prognostic factors for this group. Methods: Among the 716,566 patients recorded between 2003 and 2018 in the Polish Registry of Acute Coronary Syndromes, 104 patients aged ≥100 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
(28 reference statements)
0
2
0
1
Order By: Relevance
“…A study in Poland also demonstrated the benefit of invasive therapy in patients over 100 years of age (Piegza et al, 2020).…”
Section: Discussionmentioning
confidence: 96%
“…A study in Poland also demonstrated the benefit of invasive therapy in patients over 100 years of age (Piegza et al, 2020).…”
Section: Discussionmentioning
confidence: 96%
“…Few studies have specifically address centenarians with ACS. The Can Rapid Risk Stratification of Unstable Angina Patients Suppress Adverse Outcomes with Early Implementation of the ACC/AHA (American College of Cardiology/American Heart Association) Guidelines (CRUSADE) registry showed a poor prognosis for nonagenarians and even more so for centenarians [ 17 ] and data form the Polish Registry of ACS, including 104 centenarians with myocardial infarction, found an in-hospital mortality of nearly 35% and one-year mortality of 70% [ 18 ].…”
Section: Agementioning
confidence: 99%
“…Несмотря на относительно малое число пациентов старше 90 лет в популяции в целом, Jacek Piegza с соавт. [18] удалось изучить клинические особенности, тактику ведения и исходы у пациентов с ИМ старше 100 лет, которые составляли 0,02 % от зарегистрированной популяции в Польском регистре острых коронарных синдромов [19], являющемся основой для этого исследования. При анализе данной работы подъем сег-мента ST на ЭКГ был зарегистрирован у 51,9 % пациентов, отек легких -у 13,5 %, КШ -у 3,8 %.…”
Section: внутренние болезни Original Researchunclassified